Edukasi Pencegahan Kanker Serviks dengan Media Audiovisual terhadap Pengetahuan dan Sikap Remaja Putri - Surinati, I Dewa Ayu Ketut; Runiari, Nengah; Sipahutar, Ida Erni (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2023)
ABSTRACT The high number of cases of death due to cervical cancer in Indonesia is exacerbated by the arrival of sufferers to health services at an advanced stage of > 70%. Efforts can be made to reduce risk factors for cervical cancer through primary prevention efforts. The aim of community service is to increase teenagers' knowledge and attitudes about cervical cancer, with educational methods through audiovisual media. The level of knowledge before education was mostly sufficient 72 people (72%) and the attitude category was sufficient 70 (70%). After education there was a good increase in knowledge from 28 (26%) to 91 people (91.0%), while attitudes also existed an increase from 5 people with good attitudes to 87 people (87%). The Wilcoxon test results obtained a significant value (p) of 0.000, it can be concluded that cervical cancer prevention education is effective through audio-visual for young women. .It is hoped that health workers will increase educational activities using audio-visual methods about cervical cancer. The public, especially young women, are expected to seek information from print and electronic media about cervical cancer.